Pembelajaran IPS Terpadu Dalam Membangun Karakter Peserta Didik Sekolah Menengah Pertam - Indra Gandhi Purba, Ulung Napitu, Ira Miyarni Sustianingsih (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2024)
This research aims to analyze the Integrated Social Sciences learning process in building the character of students in junior high schools in Raya sub-district. The research method used is descriptive qualitative and library research where library research is research carried out using literature (libraries), whether in the form of books, notes or reports of previous research results. This research is a qualitative type through library study. The research stages were carried out by collecting library sources, both primary and secondary. This research classifies data based on the research formula. The research results show that the integrated social studies learning process in building the character of students in junior high school is (1) Integrated social studies learning in junior high school, (2) obstacles faced in integrated social studies learning in building the character of students in junior high school.(3) Benefits of Integrated Social Studies learning in building students' character in junior high school. 4) Integrated Social Sciences learning materials to build students' character, namely (1) Curriculum, (2) Strategy, (3) Assessment, (4) Teacher abilities.